Complexity and Resilience. - Nickain, Samaneh Sadat (River Publishers Series in Chemical, Environmental, and Energy Engineering Ser., 2021)
Processes driving urban growth are inherently related to multiple socio-economic factors, making the analysis of urban form and functions a challenging and complicated endeavour. Several fundamental factors and contextual indicators contribute to identify the main determinants of urban growth, that include economic and demographic variables, the socio-spatial structure, territorial patterns, institutional, religious and cultural attributes. Understanding spatio-temporal patterns of economic resilience can support the adoption of explicit developmental policies addressing specificities and local weaknesses of regional contexts.Thirty years after the seminal work entitled 'The Mediterranean City in Transition' by Lila Leontidou, the present contribution re-formulates a narrative framework interpreting the medium-term evolution of Southern European cities and generalises this frame to the analysis of other metropolitan areas with similar morphological and functional characteristics worldwide. Going beyond traditional Mediterranean discourses grounded on economic backwardness, social secularism, and demographic mix, an original interpretation of Mediterranean urbanities is proposed related to the local governance, real estate bubbles, land-use mix, and deregulation in urban expansion. Focusing on socioeconomic development processes in the Northern Mediterranean, the lost opportunity to reduce regional disparities and to give value to scenic and cultural values of the cities and the surrounding countryside are additional issues considered in this vision. Basing on a narrative analysis of ecologically fragile and socially fragmented Mediterranean contexts, the pervasiveness of a structural crisis - affecting regional and country economic systems, while infiltrating in the institutions, local governance systems, and the society, is finally debated as a contribution to a better understanding of complex urbanities worldwide.